The Effect Leverage, Operating Capacity, and Sales Growth On Financial Distress with Corporate Governance as Moderating Variable - Ana Mardiana; Anthony Holly (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This study focuses on examining the interplay of Corporate Governance in the context of financial ratios, including Leverage, Operating Capacity, and Sales Growth, concerning Financial Distress. The theoretical frameworks guiding this research are the pecking order theory and agency theory. To gather data, the study employs a secondary data collection method through documentary analysis. The primary data source consists of the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The sample selection process adopts the purposive sampling method, resulting in a dataset comprising 194 data points. The findings of this research reveal that Leverage exerts a significant and positive influence on Financial Distress. Conversely, Operating Capacity and Sales Growth do not exhibit any significant effects on Financial Distress. Furthermore, the Moderating Regression Analysis (MRA) conducted indicates that Corporate Governance can moderate the relationship between Leverage and Operating Capacity concerning Financial Distress. However, Corporate Governance does not have a moderating effect on the relationship between Sales Growth and Financial Distress. These results shed light on the intricate dynamics between financial ratios, Corporate Governance, and Financial Distress, offering valuable insights for practitioners and policymakers in managing and assessing the financial health of manufacturing companies in the stock exchange.